2007
DOI: 10.1002/humu.9489
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum ofMKS1andMKS3mutations in Meckel syndrome: a genotype-phenotype correlation

Abstract: Meckel syndrome (MKS) is a rare autosomal recessive lethal condition characterized by central nervous system malformations (typically occipital meningoencephalocele), postaxial polydactyly, multicystic kidney dysplasia, and ductal proliferation in the portal area of the liver. MKS is genetically heterogeneous and three loci have been mapped respectively on 17q23 (MKS1), 11q13 (MKS2), and 8q24 (MKS3). Very recently, two genes have been identified: MKS1/FLJ20345 on 17q in Finnish kindreds, carrying the same intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 19 publications
6
83
1
Order By: Relevance
“…These loci include MKS3/JBTS6 (Baala et al 2007b), NPHP1/JBTS4 (Parisi et al 2004), MKS4/NPHP6/JBTS5 (Sayer et al 2006;Valente et al 2006;Baala et al 2007a), and MKS5/NPHP8/JBTS7 (Arts et al 2007;Delous et al 2007). Notably, the genes currently identified for MeckelGruber syndrome, nephronophthisis, and Joubert syndrome are only mutated in a small percentage of affected individuals, suggesting that other loci responsible for these disorders remain to be identified (Khaddour et al 2007;Hildebrandt et al 2009). It is possible that mutations in HYLS1, distinct from the one linked to hydrolethalus syndrome, are associated with these or other ciliary disorders.…”
Section: Hydrolethalus Syndrome Is a Cilia-related Disordermentioning
confidence: 99%
“…These loci include MKS3/JBTS6 (Baala et al 2007b), NPHP1/JBTS4 (Parisi et al 2004), MKS4/NPHP6/JBTS5 (Sayer et al 2006;Valente et al 2006;Baala et al 2007a), and MKS5/NPHP8/JBTS7 (Arts et al 2007;Delous et al 2007). Notably, the genes currently identified for MeckelGruber syndrome, nephronophthisis, and Joubert syndrome are only mutated in a small percentage of affected individuals, suggesting that other loci responsible for these disorders remain to be identified (Khaddour et al 2007;Hildebrandt et al 2009). It is possible that mutations in HYLS1, distinct from the one linked to hydrolethalus syndrome, are associated with these or other ciliary disorders.…”
Section: Hydrolethalus Syndrome Is a Cilia-related Disordermentioning
confidence: 99%
“…Mutations in MKS3 are associated with a range of ciliopathies, including Joubert syndrome (34), COACH syndrome (35), and Bardet-Biedl syndrome (36), in addition to Meckel-Gruber syndrome (14,15). There are very little data regarding the effect of mutations on protein stability/function or the function of the WT protein in ciliogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 50 most highly up-regulated genes in cells expressing mutant SP-C was MGC26979/TMEM67, subsequently identified as MKS3. Genotype-phenotype analyses indicated that recessive mutations at the MKS3 locus were associated with Meckel-Gruber syndrome, a lethal disease characterized by polycystic kidneys, malformations of the liver and central nervous system, and polydactyly (14,15); however, the function of MKS3 and its role in pathogenesis are not known. The link between mutant SP-C and elevated expression of MKS3 led us to test the hypothesis that MKS3 is a component of the ERAD machinery.…”
mentioning
confidence: 99%
“…In addition, 17 other mutations listed so far for patients with the Meckel-Gruber phenotype (three nonsense, one missense, seven canonical splice-site mutations, four small deletions/duplications, one silent mutation, and one intronic 143-bp deletion, both leading to aberrant splicing). 3,12,13 TMEM216/MKS2: Three different mutations described so far in patients with Meckel-Gruber syndrome (one nonsense, one splicing, and one missense mutation). 6 TMEM67/MKS3: Wide mutational spectrum without significant hotspot mutation in non-isolated cohorts.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…So far, 37 different mutations described in patients with the Meckel-Gruber phenotype (5 nonsense, 17 missense, 7 canonical splice-site mutations, 7 small deletions/insertions/duplications, and 1 gross deletion described at genomic DNA level encompassing exons 17-21). 3,13,14 CEP290/MKS4: Recurrent mutation c.1219_1220del p.Met407fs in several families. A total of 13 different mutations described so far in patients with the Meckel-Gruber phenotype (five nonsense, two canonical splicesite mutations, and six small deletions/insertions/duplications).…”
Section: Mutational Spectrummentioning
confidence: 99%